PERAN PEMERINTAH KABUPATEN BADUNG DALAM MENGELOLA RUANG TERBUKA HIJAU (RTH) DENGAN PERSPEKTIF GOOD ENVIRONMENTAL GOVERNANCE - Swastiandari, Ida Dayu Asri; Yasintha, Putu Nomy; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2023)
The problem of environmental damage is becoming the concern of many parties. The lack of a role from the government of the Badung district office in implementing green open space management, the management of green open spaces in Badung district has only reached approximately 12% of public green open spaces and where the number for private green open spaces is 18%, which is already far exceeding than required. This has the potential to experience environmental damage along with the progress of development in all fields. Therefore, the author wants to analyze this problem by raising the title "The Role of the Badung Regency Government in handle Green Open Space (RTH) with the Perspective of Good Environmental Governance". Research Methods using qualitative research methods with a descriptive. Data were gathered by observation, interviews, and documentation, analysis using Role Theory Theory (Hendri 2003:264) Indicators of the role of personal relationships, roles related to information, decision-making roles. The findings show that the role of interpersonal relationships, related roles with information, the role of decision makers, Good Environmental Governance. it's been going well. The relationship between individuals is good, judging from the role of each stakeholder in the management of green open space. The role related to information has been shown through actors who play a role in managing Green Open Space (RTH), and coordination involving various elements of the community shows that communicationis very good, the ability to be a receiver and voter of information is also very important and can be done well. The role of decision makers has been good, as seen from the various policies implemented by the Badung district government to really help develop Green Open Space (RTH). Meanwhile, based on the GEG perspective, it is good in terms of collaborative governance. Keywords: Green Open Space , Badung, Policy